Play and Possibility: Olivia Rosenthal’s We’re Not Here to Disappear and the Limits of Understanding Alzheimer’s Disease - Tynan, Avril (Narrative Works, 2021)
Cultural representations of Alzheimer’s disease typically focus on the social and emotional burdens felt by family and friends, diluting or excluding the experience of the sufferer. This article demonstrates how narrative fiction may help us to engage with the experiences of individuals with Alzheimer’s disease by imagining what it might be like to suffer from the disease ourselves. Demonstrating the humanized and subjective understanding of Alzheimer’s disease articulated in Olivia Rosenthal’s (2007) On n’est pas là pour disparaître [We’re Not Here to Disappear (2015)] this article also exposes the limitations of narrative fiction as a means of highlighting our own ignorance in the face of others’ experiences.